Real-time monitoring wildlife using autopilot quadcopter and Wi-Fi facilities (autopilot quadcopter): article / Muhammad Saifullah Mohd Shafie - Mohd Shafie, Muhammad Saifullah (2016)
From the THE ST AR newspaper 14th April 20 15, at least five of Malaysia's mammal species, including the dugong and the Malayan tiger are now facing extinction. This is due to many causes like human activities such as logging, over-development and poaching. In Malaysia, there are no advance systems or method that can monitor the wildlife more efficient and effectively. The problem of current methods like survey on footprint and direct observation, there are no technologies on wildlife monitoring system that can visually monitor during real-time on illegal activities in remote locations. On top of that, the information need to be informed quickly when illegal incidents occurred in the forest so that the relevant authorities can be assigned to stop the illegal activity. This project is a real-time monitoring wildlife which uses an autopilot quadcopter and provides WIFI facility for the forest rangers or to the jungle trekkers. The design implementation that are carried out is by applying Monitoring tools using high definition camera with WIFI supported and night vision capable and Global Positioning System (GPS). The system is capable to improve the monitoring work in the jungle and also improves care control on wildlife effectively.